Eksistensi Hukum Keluarga Islam di Indonesia dalam Kontestasi Politik Hukum dan Liberalisme Pemikiran Islam - Athoillah Islamy (Al-Istinbath: Jurnal Hukum Islam, 2019)
This research aims to understand the existence of the Compilation of Islamic Law (KHI) and its status in the political perspective of the formation of law. In addition, it is also to understand the existence of KHI in the midst of the liberalism movement of Islamic legal thinking in Indonesia. This research is a qualitative research in the form of literature review. While the type of legal research in this study, namely historical normative legal research. There are two big conclusions from the results of this study. The First, the formation of KHI accommodates orthodox and responsive legal strategies. The second, the existence of KHI remains consistent even though there have been many thoughtful efforts and studies that have criticized it. This is due to the criticism only as the impact of the opening of the democratic climate for the liberal movement of Islamic thought in the public sphere.